Criminal Liability for Violence Against Minors in the “Geng Konten” Case in Cirebon - Winata Yudistira; Alip Rahman (Journal of Social Research, 2026)
Violence against children remains a pressing human rights issue, with long-term physical, psychological, and social consequences. The emergence of social media has introduced new forms of violence, where adolescents engage in aggressive acts not only to resolve conflict but also to gain recognition and social status in digital spaces. This phenomenon is evident in the content gang cases in Cirebon, where violence is orchestrated, recorded, and disseminated online. The purpose of this study is to examine the qualifications of perpetrators, the construction of criminal responsibility in group-perpetrated violence against minors, and the appropriate legal and criminal implications for both adult and juvenile offenders in the context of social media-based violence. The study employs a normative legal research method with statutory and conceptual approaches, analyzing relevant provisions in the Indonesian Criminal Code, the Child Protection Law, and related doctrines on participation and intent. The findings indicate that perpetrators include direct actors, planners, and content distributors, and that collective acts of violence satisfy the elements of criminal liability under Articles 55, 56, and 170 of the Criminal Code, often applying dolus eventualis. The study concludes that law enforcement must ensure proportionate punishment, differentiate between juvenile and adult offenders, and adopt adaptive and preventive strategies to address the growing impact of digital content-related violence.